THE EFFECT OF MODIFIED COGNITIVE LOAD THEORY PROBLEM BASED LEARNING MODELS TO PROBLEM SOLVING ABILITIES - Wafa Azimah; Aan Hendrayana; Abdul Fatah (MATEMATIKA DAN PEMBELAJARAN, 2020)
The aim of this study is to determine the effect of the modified Problem Based Learning Model with Cognitive Load Theory to students problem solving abilities. This research was conducted in SMP Negeri 1 Cilegon City in the academic year 2019/2020 with the sample used was class of VII A as an experimental class using CLT-modified PBL models and class of VII E as a control class that gained learning with the usual PBL models. The research method used in this study is a mix methods of the concurrent embedded model with quantitative methods as the primary method and qualitative as a secondary method. The results and discussion of the study showed that the achievement and improvement of the problem solving ability of the experimental class was better than the control class. So it can be concluded that there is a positive influence on CLT modified PBL models on student’s problem solving abilities. In addition, the amount of cognitive load possessed by students while learning can be one of the main factors that can affect student’s problem solving abilities. It is believed that reducing extraneous cognitive load can improve student's problem solving abilities.